Bile Acids, Liver Cirrhosis, and Extrahepatic Vascular Dysfunction - Sauerbruch, Tilman; Hennenberg, Martin; Trebicka, Jonel; Beuers, Ulrich (Frontiers in Physiology, 2021)
The bile acid pool with its individual bile acids is modulated in the enterohepatic circulation by the liver as the primary site of synthesis, the motility of the gallbladder and of the intestinal tract, as well as by bacterial enzymes in the intestine. The nuclear receptor FXR and TGR5 are important set screws in this process. Bile acids have a vasodilatory effect, at least according to in vitro studies. The present review examines the question of the extent to which the increase in bile acids in plasma could be responsible for the hyperdynamic circulatory disturbance of liver cirrhosis and whether modulation of the bile acid pool, for example, via administration of UDCA or via modulation of the dysbiosis present in liver cirrhosis could influence the hemodynamic disorder of liver cirrhosis. According to our analysis, the evidence for this is limited. Long-term studies on this question are lacking.